Form over function: an analysis of Midjourney-generated infographics - C Klohn Reader, Sara; Iacob, Alis (InfoDesign, 2024)
Text-to-image generative models are a topic of great discussion in design. Seeking to understand the potential impact of these technologies on graphic design, this think piece paper presents preliminary insights from an explorative study that looked at 23 infographics generated by the popular platform Midjourney in 2023. The results indicated that, while the Midjourney outputs were at first glance plausible, upon closer examination these failed to solve a design problem. The repetitive layouts, the unintelligible textual elements and the disregard for purpose, context and audience, indicated that Midjourney is not currently producing infographics as understood by the design community. While not definitive, this study intends to contribute to the ongoing discussions in the wider field of AI and graphic design.